Exploring the Effect of Digital Economy on PM2.5 Pollution: The Role of Technological Innovation in China - Sun, Xiangxiang; Chen, Zhangwang; Loh, Lawrence (Frontiers in Environmental Science, 2022)
PM2.5 emission causes serious harm to health and hinders the sustainable development of economy and society. Among all the factors affecting PM2.5 pollution, there is a lack of understanding of the role of new economic forms and information technology innovation. This study aims to explore the impact of digital economy on PM2.5 pollution and its influencing mechanism. The empirical results demonstrate that digital economy has a significant negative impact on PM2.5 pollution during the investigated period. In other words, the digital economy is conducive to alleviating PM2.5 pollution. Further analysis shows that the digital economy promotes technological innovation, which is an important mediating mechanism affecting PM2.5 pollution. Additionally, the inhibitory effect of digital economy on PM2.5 pollution is more significant in the eastern and central regions. Unfortunately, the negative impact of digital economy on PM2.5 pollution is not significant in the western region. The conclusions provide a new strategy for reducing pollution emissions and improving environmental quality.